The world's water : the biennial report on freshwater resources - Gleick, Peter H. (The World's Water, 2014)
Produced biennially, The World's Water is the most comprehensive and up-to-to date source of information and analysis on freshwater resources. Each new volume examines critical global trends and offers the best data available on a variety of topics related to water. Volume 8 features chapters on hydraulic fracturing (fracking), water footprints, sustainable water jobs, and desalination financing, among other timely issues. Water briefs provide concise updates on topics including the Dead-Sea and the role of water in the Syrian conflict. The World's Water is coauthored by MacArthur "genius" Peter H. Gleick and his colleagues at the world-renowned Pacific Institute. Since the first volume was published in 1998, the series has become an indispensable resource for professionals in government agencies and nongovernmental organizations, researchers, students, and anyone concerned with water and its use.